Comptabilités et sociétés - Côté, Yves-Aubert (Assurances)

(untitled) (HEC Montréal, 1992)
No one today will dispute the key role accounting plays in management. Accounting is in fact one of the essential tools managers use each day to accomplish their task. lt is however, not as easy to appreciate the extent to which this discipline has been shaped and influenced by social factors. Basing himself on the premise that accounting does not exist in a vacuum, the author examines this activity from the Middle Ages to the Modern era to show how it has evolved and continues to evolve in response to social, economic and political change. This text was the basis of a presentation made at an international seminar on new trends in management held in June 1986 at l’École des Hautes Études Commerciales in Montréal.